Konsep Elemen Ruang Imajinatif melalui Pola Inhabitation dengan Materialitas Virtual pada Perpustakaan - Athifa Pradya Ayutaffana; Bambang Soemardiono; Arina Hayati (Universitas Sebelas Maret Surakarta, 2024)
This paper explores the initial stages of design from issues, context, to problems related to the development of real and virtual technology, especially the phenomenon of inhabitation in the library building. The aim of this design-based research is to increase motivation and learning effectiveness, as well as maintain the function of the physical library building in the future with integrative virtual technology. The data collection method uses literature reviews as secondary data, and naturalistic research methods as primary data to validate theory and produce aspects and principles of inhabitation in real and virtual contexts that can be applied in library.. The results of this research are the concept of imaginative space elements that represent inhabitation patterns in various interactions and atmospheres in library design. The benefit of the research is knowing how the integrative application of technology in libraries can improve and develop the function of reading and learning spaces interactively and effectively.